(untitled) (Research, Society and Development, 2023)
As you age, the facial support structure weakens and you lose facial fat, so that the most affected areas are the cheeks, areas close to the eyes, neck and eyebrows. This research aims to carry out a literature review of scientific articles on the use of polydioxanone threads (PDO) and hyaluronic acid (HA). The bibliography review was performed using Google Scholar. The inclusion criteria are articles published from 2018 to 2022. As for the exclusion criterion, articles that did not address the theme or that were prior to 2018 were used. The descriptors used were: sustaining threads, polydioxanone and hyaluronic acid. 38 articles were recalled and 10 articles that met the inclusion criteria were selected, after being carefully read and analyzed. It is considered, through what was verified in the research for the construction of the work, that the aesthetic procedures using the threads of polydioxanone (PDO) and hyaluronic acid for facial rejuvenation are an innovation that comes to collaborate for the improvement of the aesthetic aspects, as well -being and quality of life of the individual. The safety and health of the patient must be taken into account, so it would be indicated that more and more research should be carried out to make such procedures less and less invasive.